Eugenol Reduced ΜPO, CD45 and HMGB1 Expression and Attenuated the Expression of Leukocyte Infiltration Markers in the Intestinal Tissue in Biliopancreatic Duct Ligation-Induced Pancreatitis in Rats - Panagoula Oikonomou; Christina Nikolaou; Fotini Papachristou; Apostolos Sovatzidis; Maria Lambropoulou; Charikleia Giouleka; Vasileios Kontaxis; Dimitrios Linardoutsos; Apostolos Papalois; Michael Pitiakoudis; Alexandra Tsaroucha (Medicina, 2023)
Background and Objectives: Inflammation and dysregulation in the intestinal barrier function in acute pancreatitis (AP) trigger pancreatic lesions, systemic inflammatory response, and multiple organ dysfunction. Eugenol, as the main component of clove (Syzygium aromaticum), is known for its antioxidant and anti-inflammatory properties. We studied the potentially beneficial effect of eugenol in a rodent model of biliopancreatic duct ligation-induced AP. Materials and Methods: Rats were randomly divided into three groups: Sham, AP, and AP + eugenol (15 mg/kg/day). Serum TNFα, IL-6, IL-18, and resistin levels, as well as IL-6, TNFα, MPO, HMGB1, and CD45 tissue expression, were determined at various timepoints after the induction of AP. Results: Eugenol attenuated hyperemia and inflammatory cell infiltration in the intestinal mucosal, submucosal, and muscular layers. IL-6 and resistin serum levels were significantly reduced in the AP + eugenol group, while serum TNFα and IL-18 levels remained unaffected overall. TNFα pancreatic and intestinal expression was attenuated by eugenol at 72 h, while IL-6 expression was affected only in the pancreas. MPO, CD45, and HMGB1 intestinal expression was significantly reduced in eugenol-treated rats. Conclusions: Eugenol managed to attenuate the inflammatory response in the intestine in duct ligation-induced AP in rats.